2012
DOI: 10.1037/a0028907
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among client and counselor agreement about the working alliance, session evaluations, and change in client symptoms using response surface analysis.

Abstract: Two studies explored how counselor and client agreement on the therapy alliance, at the beginning of treatment, influenced early session evaluations and symptom change. Unlike prior studies that operationalized alliance convergence as either a profile similarity correlation or a difference score, the present study used polynomial regression and response surface analysis to examine agreement. Study 1 explored the impact of working alliance congruence on session depth and smoothness at the 3rd session of treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
155
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(177 citation statements)
references
References 61 publications
18
155
4
Order By: Relevance
“…It follows that taking a more active approach may improve therapists’ attunement to fluctuations in the alliance. These suggestions are also consistent with previous findings showing that therapists who rated themselves as generally forming stronger real relationships also rated poorer treatment progress (Kivlighan, Gelso, Ain, Hummel, & Markin, 2014), and with findings showing that patients rated sessions less smooth when their ratings of the alliance were lower than their therapists’ ratings of the alliance, and they rated sessions as more smooth when their ratings of the alliance were higher than their therapists’ ratings of the alliance (Marmarosh & Kivlighan, 2012). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It follows that taking a more active approach may improve therapists’ attunement to fluctuations in the alliance. These suggestions are also consistent with previous findings showing that therapists who rated themselves as generally forming stronger real relationships also rated poorer treatment progress (Kivlighan, Gelso, Ain, Hummel, & Markin, 2014), and with findings showing that patients rated sessions less smooth when their ratings of the alliance were lower than their therapists’ ratings of the alliance, and they rated sessions as more smooth when their ratings of the alliance were higher than their therapists’ ratings of the alliance (Marmarosh & Kivlighan, 2012). …”
Section: Discussionsupporting
confidence: 91%
“…Similar patterns of inconsistent results were reached when focusing on other aspects of the therapeutic relationship, such as the real relationship (Gelso et al, 2012; Markin, Kivlighan, Gelso, Hummel, & Spiegel, 2014). Additionally, although some studies showed that agreement between therapist and patient on the therapeutic alliance can predict outcome (Bachelor, 2013; Kivlighan, 2007; Marmarosh & Kivlighan, 2012; Rozarmin et al, 2008), others failed to find a significant association between differences in therapist and patient alliance levels and outcome (Fitzpatrick, Iwakabe, & Stalikas, 2005) or dropout (Meier & Donmall, 2006). …”
mentioning
confidence: 99%
“…Theoretically, this might reflect an ongoing negotiation of the therapeutic relationship that becomes more attuned as the relationship evolves; that is, whatever the state of the relationship, the participants are able to read it more similarly whether it is thriving or in rupture. Second, and also consistent with limited prior research (Marmarosh & Kivlighan, 2012), we hypothesized that alliance perspective discrepancy measured in early therapy would be associated with less depression reduction (or, conversely, that greater alliance perspective similarity would be associated with greater depression reduction). Third, we predicted that convergence in patient-therapist alliance ratings over the course of therapy would be associated with greater depression reduction.…”
supporting
confidence: 65%
“…A small literature has used both patient and therapist data together when considering alliance discrepancy/similarity at a particular time point and divergence/convergence over time. For example, one study examined patient-therapist alliance rating similarity at the third session of psychotherapy for 63 therapy dyads from counseling clinics (Marmarosh & Kivlighan, 2012); the authors found that more similarity was related to greater symptom improvement. This finding, though, was specific to therapy dyads with higher-rated alliances, suggesting an interaction between early alliance levels and patient-therapist perceptual similarity of their alliance.…”
mentioning
confidence: 99%
“…Unfortunately, PSIs are conceptually ambiguous, discard important fit information, and are not sensitive to rater differences (Edwards & Parry, 1993;Marmarosh & Kivlighan, 2012). Therefore, Edwards and Parry (1993) advocated polynomial re gression and response surface analysis to as sess person-group fit as an alternative to PSIs.…”
Section: Person-group Fitmentioning
confidence: 98%